2011
DOI: 10.1002/pssc.201001067
|View full text |Cite
|
Sign up to set email alerts
|

Growth temperature and growth rate dependency on reactor pressure for InN epilayers grown by HPCVD

Abstract: This contribution presents results on achievable growth temperatures and growth rates as a function of reactor pressure for the growth of InN by high‐pressure chemical vapour deposition (HPCVD). The InN epilayers were grown at reactor pressures ranging from atmospheric pressure to 19 bar. The results show that the InN growth temperature increased linearly with the reactor pressure from 759 °C to 876 °C. The growth rate decreases from 127 nm/h to 20 nm/h as the reactor pressure is increased from 1 bar to 19 bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…8, the growth rate decreases linearly with increasing reactor pressure as observed in the previous study. 12 As the diffusion layer thickness decreases inversely proportional to the square root of the pressure, a similar behavior would be expected for the growth rate in the transport limited growth regime. The InN layer grown at 2.5 bar has a large processing error, as in our present reactor the flow channel height is fixed at 1 mm and cannot be adjusted for the variation in the diffusion layer thickness as function of the reactor pressure.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…8, the growth rate decreases linearly with increasing reactor pressure as observed in the previous study. 12 As the diffusion layer thickness decreases inversely proportional to the square root of the pressure, a similar behavior would be expected for the growth rate in the transport limited growth regime. The InN layer grown at 2.5 bar has a large processing error, as in our present reactor the flow channel height is fixed at 1 mm and cannot be adjusted for the variation in the diffusion layer thickness as function of the reactor pressure.…”
Section: Resultsmentioning
confidence: 54%
“…The growth temperatures were adjusted for each reactor pressure to obtain optimum crystallinity. The growth temperature increases linearly with reactor pressure from 750 to 865 C. 12 The InN deposition process consists of the following steps: First, the substrate was heated to the growth temperature and exposed to a constant ammonia flow of 1200 sccm for 5 min. Afterward, an InN nucleation layer was deposited with a group-V/III ratio of 2400 for 1 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were grown with HPCVD at 15 bar reactor pressure and temperatures around 1,150 K, while the NH 3 /TMI ratio was 2500. XRD measurements revealed for the sample single phase InN(0002) with hexagonal symmetry (Buegler et al 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Previous work addressed the effect of reactor pressure on the growth temperature, growth rate, crystalline quality and carrier concentration values of InN by analysing respective Fourier transform infrared reflectance spectra (FTIR) [10]. The analysis showed that the structural quality of InN layers improves with increasing reactor pressure and the growth rate decreases due to the reduction of boundary layer thickness with increasing reactor pressure [9,10]. The present work shows improved crystallinity together with decreased optical band gap and carrier concentration values with increasing reactor pressure.…”
Section: Introductionmentioning
confidence: 99%